3D homogenisation of concentrated windings with rectangular conductors - Romanazzi, P; Ayat, S; Wrobel, R; Howey, D (IEEE, 2017)
Design optimisation of electromagnetic devices is strongly affected by thermal behaviour. In order to check whether thermal limitations are exceeded, one has to accurately evaluate the loss generated for each working condition and feed it to a thermal model. Using the two models in sequential manner, however, can lead to an error in the loss estimation. Moreover, a proper loss distribution calculation allows for a more precise temperature field computation, allowing for an accurate prediction of the hot-spot temperature. When AC effects are significant, this process becomes more computationally expensive since every single wire should be included in the model and this inevitably slows the design procedure. In this work a method is presented for model order reduction of coupled 3D electromagnetic-thermal finite element analysis via homogenisation. The method, applied to an hardware exemplar representative of an open-slot modular stator-winding assembly, is demonstrated to provide very accurate results compared to a fine model where every single conductor is taken into account, but with a significant reduction in simulation time. Extensive experimental validation is also provided. Due to the reduction in computational effort, the method is suitable for improving the design process and reducing the time to market of many electromagnetic devices, including electrical machines, inductors and transformers.